SOCIAL CONTROL METHODS OF DELINQUENT SUBCULTURES (Eureka Journal of Humanities and Social Research, 2026)
This article analyzes the causes of the formation of delinquent subcultures, their social essence and modern methods of their management. The study considers social inequality, marginalization, youth problems and cultural transformations as the main factors of delinquent behavior. It also covers the theoretical foundations of social management, the interrelationship of prevention, rehabilitation and social control mechanisms. The article analyzes the experience of different societies using systematic, comparative and empirical methods. The cooperation of state, civil society and family institutions is justified as an important factor in the effective management of delinquent subcultures. The results of the study serve to ensure social stability, prevent negative behavior among young people and create a healthy social environment.
Keywords: Delinquency, subculture, social management, prevention, rehabilitation, social control, youth, deviant behavior, culture, social environment, inequality, transformation